OP0060 Efficacy and Safety of Tocilizumab in Patients with Polyarticular Juvenile Idiopathic Arthritis: Data from a Phase 3 Trial. (23rd January 2014) - De Benedetti, F.; Ruperto, N.; Zuber, Z.; Keane, C.; Harari, O.; Kenwright, A.; Cuttica, R.; Keltsev, V.; Xavier, R.; Calvo, I.; Nikishina, I.; Rubio-Pérez, N.; et al.
Abstract : Background: Elevated IL-6 levels are associated with disease activity in patients (pts) with juvenile idiopathic arthritis (JIA). 1 Tocilizumab (TCZ), an IL-6 receptor inhibitor, was evaluated for the treatment of polyarticular-course JIA (pcJIA; RF+ and RF– poly- and extended oligoarticular JIA) in the CHERISH study. Methods: CHERISH is a 104-wk study in pts age 2-17 y with active pcJIA for ≥6 mo who failed MTX. Prior to wk 16, all pts received open-label (OL) TCZ every 4 wks (if body weight [BW] ≥30 kg, 8 mg/kg [n=119]; if BW <30 kg, pts randomly assigned to 8 mg/kg [n=34] or 10 mg/kg [n=35]). At wk 16, eligible pts (with ≥JIA ACR30 response) entered a 24-wk randomised (pts assigned [1:1] to placebo [PBO] or to continue TCZ at the same dose), double-blind (DB) withdrawal period for evaluation of the primary endpoint (JIA ACR30 flare relative to wk 16). Pts who flared or completed the DB period entered an OL extension and received the same TCZ dose as in the lead-in period. Efficacy data (until wk 40) are presented for the ITT population; safety data based on 184.4 pt-y (PY) of exposure are presented. Results: 188 pts entered the OL lead-in period (77% female; 79%/46% receiving concurrent MTX/oral corticosteroids [CS], respectively). 22 (12%) pts withdrew from the OL extension (15 pts [8%] insufficient response; 3 [2%] adverse events [AEs]; 4 [2%] other reasons), and 166 pts entered the DB period. Efficacy responses at the end of the OL extension at wk 16 are shown (Table). At wk 40, the primary endpoint was met (48.1% PBO pts vs 25.6% TCZ pts), and JIA ACR30/50/70 responses were significantly higher with TCZ than PBO (Table). The degree of improvement at wk 16 was lower for these endpoints in the TCZ 8 mg/kg <30 kg BW group than in the other 2 TCZ groups (Table). At the safety data cut, 184 PY of follow-up had occurred in the 188 pts enrolled. Rates/100PY of AEs and SAEs were 480 and 12.5, respectively; infection was the most common AE (164/100PY) and SAE (4.9/100PY). ALT/AST elevations ≥3× ULN occurred in 3.7%/<1% of pts, neutropenia (<1000 cells/mm3) in 3.7% of pts, thrombocytopenia (<50, 000 cells/mm3) in 1.1% of pts and LDL-cholesterol ≥110 mg/dl in 11.4% of pts. Image/graph: Conclusions: The CHERISH trial supports that TCZ treatment in pcJIA is efficacious and leads to a sustained clinically meaningful improvement with a monthly regimen at doses of 8 mg/kg if BW ≥30 kg and 10 mg/kg if BW <30 kg. The safety profile is consistent with that in other TCZ-treated pts. 2 References: Clin Exp Rheumatol . 1992;493; Ann Rheum Dis 2011;70(S3):67 Disclosure of Interest: F. De Benedetti Grant/research support from: Abbott, Pfizer, BMS, Roche, Novimmune, Novartis, SOBI, N. Ruperto Grant/research support from: Abbott, AstraZeneca, BMS, Centocor, Lilly, Francesco Angelini, GSK, Italfarmaco, Merck Serono, Novartis, Pfizer, Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences, Xoma, Wyeth, Consultant for: (fees received by organization) Abbott, AstraZeneca, BMS, Centocor, Lilly, Francesco Angelini, GSK, Italfarmaco, Merck Serono, Novartis, Pfizer, Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences, Xoma, Wyeth, Speakers bureau: Abbott, Boehringer, BMS, Novartis, Astellas, Italfarmaco, MedImmune, Pfizer, Roche, Z. Zuber: None Declared, C. Keane Employee of: Roche, O. Harari Employee of: Roche, A. Kenwright Employee of: Roche, R. Cuttica Grant/research support from: Roche, Novartis, Lilly, Centocor, Consultant for: Roche, Novartis, Centocor, Pfizer, Speakers bureau: Roche, Pfizer, BMS, Novartis, V. Keltsev: None Declared, R. Xavier: None Declared, I. Calvo: None Declared, I. Nikishina: None Declared, N. Rubio-Pérez: None Declared, E. Alekseeva: None Declared, V. Chasnyk: None Declared, J. Chavez: None Declared, G. Horneff Grant/research support from: Abbott, Pfizer, Speakers bureau: Abbott, Pfizer, Novartis, Roche, Chugai, V. Opoka-Winiarska: None Declared, P. Quartier Grant/research support from: Abbott, Novartis, Pfizer, Consultant for: Novartis, Abbott, Pfizer, BMS, Roche, C. Silva Grant/research support from: Roche, E. Silverman: None Declared, A. Spindler: None Declared, A. Martini Grant/research support from: Abbott, AstraZeneca, BMS, Centocor, Lilly, Francesco Angelini, GSK, Italfarmaco, Merck Serono, Novartis, Pfizer, Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences, Xoma, Wyeth, Consultant for: (fees received by organization) Abbott, AstraZeneca, BMS, Centocor, Lilly, Francesco Angelini, GSK, Italfarmaco, Merck Serono, Novartis, Pfizer, Regeneron, Roche, Sanofi Aventis, Schwarz Biosciences, Xoma, Wyeth, Speakers bureau: Abbott, BMS, Astellas, Boehringer, Italfarmaco, MedImmune, Novartis, Pfizer, D. Lovell Grant/research support from: National Institutes of Health, Consultant for: AstraZeneca, Centocor, Wyeth, Amgen, BMS, Abbott, Pfizer, Hoffmann-La Roche Novartis, UCB, Forest Research, H. Brunner Shareholder of: PRCSG, Grant/research support from: National Institutes of Health, Lupus Foundation, Cincinnati Center for Clinical and Translational Research, Consultant for: Roche, Novartis, GSK, Medimmune, Pfizer, BMS